Climate change and global warming effects on agricultural‎ communities: Mitigation through pedagogical content knowledge (PCK) approach - Mahbod, Mina (International Journal of Applied and Experimental Biology, 2025)
This article examines the effects and changes of climate change and global warming on farming communities and their social life, especially in coastal and arid regions. In the study, the PRISMA approach and the C-I-M-O framework were employed to survey scientific publications in the context of environmental, social, and psychological impacts of climate change and global warming. Resultantly, this paper discusses the opportunities and challenges for adaptation and mitigation, and the strategies and methods for minimizing the impacts of climate change on the farming communities. At the bottom-line, it proposes the need for more research, PCK approach education, awareness, and actions regarding these phenomena, alongside the role of policymakers and institutions in addressing the challenges and implications of climate change. In conclusion, a passive call felt for a multidisciplinary and cooperative response from various stakeholders, such as scientists, practitioners, policymakers, and civil society, to create a more resilient, sustainable, and healthy future for humans and the planet.